Bezrobocie a polityka monetarna Polski w latach 2003-2004 - Linek, Stefan; Noga, Marian (Unemployment and Monetary Policy in Poland between 2003 and 2004, 2006)
This paper presents the influence of monetary policy in Poland on unemployment during the last two years. The authors confirm that monetary policy was adequate restrictive during this period. According to such monetary policy, unemployment in Poland didn't rise during the research period.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1138, s. 9-16